Combined Effects of Compound Low-Sodium Alternative Salts and Vacuum Tumbling on the Quality, Water Distribution, and Microstructure of Marinated Beef - Yanfeng Huang; Shujie Yang; Longtao Zhang; Song Miao; Zhiyong Xu; Baodong Zheng; Kaibo Deng (Foods)
This study proposes a compound low-sodium alternative salt (CLSAS) formulation (2.4% sodium chloride, 0.8% K lactate, 0.4% magnesium chloride, 0.4% Ca ascorbate, 0.2% L lysine, and 4% sorbitol) combined with vacuum tumbling for beef marination. The effects of 4% NaCl static marination (F), CLSAS static marination (L), and CLSAS vacuum tumbling (VT-L) on the physicochemical properties, water distribution, and microstructure of marinated beef were evaluated. Compared with F, L maintained similar yield and color, reduced cooking loss, and improved texture while lowering sodium content. VT-L further enhanced product yield, water content, color, texture, and tenderness. Both CLSAS and vacuum tumbling reduced the relaxation time of immobilized water, promoted orderly formation of protein structure, and altered the microstructure of myogenic fibers. VT-L additionally improved the water-holding capacity of myofibrils and further reduced the relaxation times of immobilized and free water. Overall, VT-L could be an effective approach for enhancing the quality of low-sodium meat products, providing a feasible basis for the industrial application of CLSAS for low-sodium marinated meat products.